2011
DOI: 10.1021/jp1093492
|View full text |Cite
|
Sign up to set email alerts
|

On the Munn−Silbey Approach to Polaron Transport with Off-Diagonal Coupling and Temperature-Dependent Canonical Transformations

Abstract: Improved results using a method similar to the Munn-Silbey approach have been obtained on the temperature dependence of transport properties of an extended Holstein model incorporating simultaneous diagonal and off-diagonal exciton-phonon coupling. The Hamiltonian is partially diagonalized by a canonical transformation, and optimal transformation coefficients are determined in a self-consistent manner. Calculated transport properties exhibit substantial corrections on those obtained previously by Munn and Silb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…To gain a better understanding, further investigations based on a dynamical treatment of the nonlocal e-ph couplings are clearly needed. We note that previous studies based on the variational principle have demonstrated that the nonlocal e-ph couplings can renormalize the electronic band by introducing new minima and ultimately lead to its broadening [43,44], which, in line with our analysis above, could indeed result in smaller band effective masses. However, the band effective mass should not be confused with the optical effective mass since the latter, which is obtained from the f -sum rule [Eq.…”
Section: Optical Conductivity and Optical Effective Masssupporting
confidence: 89%
“…To gain a better understanding, further investigations based on a dynamical treatment of the nonlocal e-ph couplings are clearly needed. We note that previous studies based on the variational principle have demonstrated that the nonlocal e-ph couplings can renormalize the electronic band by introducing new minima and ultimately lead to its broadening [43,44], which, in line with our analysis above, could indeed result in smaller band effective masses. However, the band effective mass should not be confused with the optical effective mass since the latter, which is obtained from the f -sum rule [Eq.…”
Section: Optical Conductivity and Optical Effective Masssupporting
confidence: 89%
“…(3) as the antisymmetric and symmetric nonlocal e-ph coupling mechanism, respectively. The case where a single mode per molecule is considered and the symmetric coupling mechanism is neglected, υ s = 0 (i.e., υ n+1 = −υ n ), corresponds to the standard SSH model; starting with the work of Munn and Silbey 8 , it is the most commonly used model to describe charge transport in organic semiconductors 9,[11][12][13]17,19 . The two coupling mechanisms lead to rather different interaction patterns.…”
Section: Modelmentioning
confidence: 99%
“…On the other hand, there is currently a growing consensus that the nonlocal e-ph coupling mechanism plays an important or even dominant role in organic semiconductors 1,[7][8][9][10][11][12][13][14][15][16][17][18][19] . Although a detailed quantum-chemical investigation of the nonlocal e-ph coupling has been performed to date only for a few systems [14][15][16] , the results underline that the nonlocal e-ph coupling mechanism can be very complex and, depending on the nature of the relevant phonon modes, can result in different dynamical disorder patterns.…”
mentioning
confidence: 99%
“…However, in the literature, little attention has been paid to the Hamiltonians containing the off-diagonal exciton-phonon coupling due to inherent difficulties to obtain reliable solutions [23], especially for the polaron dynamics [24]. Early treatments of off-diagonal coupling include the Munn-Silbey theory [25,26] which is based upon a perturbative approach with added constraints on canonical transformation coefficients determined by a self-consistency equation. The global-local (GL)Ansatz [27,28], formulated by Zhao et al in the early 1990s, was later employed in combination with the dynamic coherent potential approximation (with the Hartree approximation) to arrive at a stateof-the-art ground-state wave function as well as higher eigenstates [29].…”
Section: Introductionmentioning
confidence: 99%